Cause of and contributing factors to maternal deaths; a cross‐sectional study using verbal autopsy in four districts in Bangladesh. (September 2014) - Halim, A; Utz, B; Biswas, A; Rahman, F; van den Broek, N
Abstract : Verbal autopsy used at community level is an accepted method to identify cause of death and factors contributing to death. Maternal deaths occurring in four districts in Bangladesh over a period of 24 months were identified and community health workers were trained to conduct a verbal autopsy. Of 571 maternal deaths identified almost half (273, 47.8%) occurred at facility level, 97 (17.0%) died en route to a healthcare facility and 201 (35.2%) maternal deaths occurred at home. The majority of maternal deaths occurred in the postpartum period (78.8%) in the first 6 hours after giving birth (41.6% of all postpartum deaths). Women who had accessed care at a healthcare facility were less likely to die in the first 6 hours when compared with women who died at home (relative risk 0.70; 95% confidence interval 0.56–0.88) 70.4% (402) of deaths were classified as direct maternal deaths, 12.4% (71) as indirect and 13.8% (79) as unspecified. The most common cause of death was haemorrhage (38%), followed by eclampsia (20%) and sepsis (8.1%). Almost three out of four women who died had sought care for complications during the index pregnancy. Most mothers who died in Bangladesh had accessed care. It is now crucial that the quality of care received at health facility level is improved. This includes a refocus on strengthening healthcare providers' knowledge and skills to recognise and manage complications and provide emergency obstetric care. The enabling environment must be in place as well as ensuring a fully functional referral pathway between healthcare facilities.